Mini Aquatec Mobilize General Plan Design as a Means of Increasing Food Security Through Cultivation and Ecotourism - Nely Handayani Kusuma Hadi; Anauta Lungiding Angga Risdianto; Triyanti Irmiyana; Ratna Ayu Pawestri Kusuma Dewi; Mohammad Abdullah (National Research and Innovation Agency (BRIN Publishing), 2023)
The Mini Aquatec Mobilize design is an innovation given as the development of a floating chart, which is currently used as a place for fish farming. This development aims to optimize the function of a crab for cultivation, fishing, and tourism. It is placed on the cruise line 5 miles from the coast, with coverage of the coastal area of Madura. Through this innovation, food security is hoped to increase through fish farming and ecotourism for the community. The purpose of this study is to design a general plan. The general plan is a drawing to determine the location of the rooms, equipment, and the amount of equipment on board in 2D form. The method used uses a comparison ship, which is then carried out by making designs through application assistance. From the research, the main ship dimensions were L = 15.00 m, B = 4.00 m, H = 1.71 m, and T = 0.86 m. With a total of 20 passengers and the need for lights for aquaculture, namely 2 (20 watts) deck lights, 2 (500 watts) spotlights and 12 (15 watts) decoy lights.